2014
DOI: 10.1590/0103-5150.027.003.ao13
|View full text |Cite
|
Sign up to set email alerts
|

Postural biomechanical risks for nursing workersRiscos biomecânicos posturais em trabalhadores de enfermagem

Abstract: Introduction In the hospital environment, several types of professionals must be involved in continuous working shifts, under working conditions that are often unsatisfactory. Objective The objective of the present study was to analyze the biomechanical risk factors for work-related musculoskeletal disorders (WRMD). Material and methods This was a cross-sectional, exploratory, descriptive and quantitative study and its analysis considered 15 workers, in three shifts. A questionnaire containing personal informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…The studies of Alexopulus et al (2003) and Smith et al (2006) reported that shoulder WRMSD are associated with strenuous shoulder movement, repetitive tasks, and manual handling. Abdalla et al (2014) employed the Rapid Entire Body Assessment (REBA) method to investigate a series of tasks commonly performed by HCWs (e.g., handling the bed cranks, disposal of materials, bed bath, placing patients in bed, etc. ), suggesting that they are characterized by excessive biomechanical exposure of both the spine and UL.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Alexopulus et al (2003) and Smith et al (2006) reported that shoulder WRMSD are associated with strenuous shoulder movement, repetitive tasks, and manual handling. Abdalla et al (2014) employed the Rapid Entire Body Assessment (REBA) method to investigate a series of tasks commonly performed by HCWs (e.g., handling the bed cranks, disposal of materials, bed bath, placing patients in bed, etc. ), suggesting that they are characterized by excessive biomechanical exposure of both the spine and UL.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação aos fatores de riscos biomecânicos, os distúrbios osteomusculares estão relacionados à jornada de trabalho superior ao normal, considerando-se a frequência semanal e o tempo diário de trabalho 18 .…”
Section: Reflexão Sobre As Condições De Trabalho Da Equipe De Enfermagemunclassified
“…Com base no exposto, o profissional de Educação Física propõe uma análise do ambiente e do cuidado para mapeamento postural durante as quatro horas de interação entre profissional de enfermagem e paciente para investigar a ergonomia voltada à preservação da saúde postural, a recuperação do bem-estar e a promoção de uma condição física mais saudável durante o cuidado na sessão de hemodiálise, coadunando com estudiosos na temática (ABDALLA et al, 2014); FONTANA, 2014).…”
Section: Introductionunclassified